DAMPAK PAKTA PERTAHANAN TRILATERAL AUKUS TERHADAP KONDISI REGIONAL INDO-PASIFIK - Mariane Olivia Delanova (Dinamika Global : Jurnal Ilmu Hubungan Internasional, 2021)
This article was compiled to discuss the AUKUS Trilateral Defense Pact which is a collective security effort taken from the aggressiveness appointed by China in the Indo-Pacific region. There have been a variety of positive and negative responses from Australia from countries in the region, particularly China, which views the defense pact as a very responsible threat and an open challenge to their growing influence in the Indo-Pacific. This discussion is important because AUKUS is considered to be very detrimental to regional peace and security, and endangers efforts to destroy nuclear weapons, although it can be considered that this agreement will be a decisive step taken to take predatory tendencies from China. On the purpose of AUKUS and the reasons why Australia is more concerned with security than what is examined in this article, considering the ownership of supported vessels will support Australia's understanding to carry out longer patrols to maintain the Indo-Pacific security conditions that are often caused by the presence of a strong Chinese military in the area. AUKUS will be an important action in building the foundation that becomes a barrier for China to stop confronting other countries, commit violations at the borders of the Indo- Pacific region, and as a retaliation for aggressive actions against several countries in the region.